Human Umbilical Cord Mesenchymal Stem Cells Inhibit T Follicular Helper Cell Expansion through the Activation of iNOS in Lupus-Prone B6.MRL-Fas(lpr) Mice - Zhang, Zhuoya (Cell Transplant, 2017)
The aberrant generation or activation of T follicular helper (Tfh) cells contributes to the pathogenesis of systemic lupus erythematosus (SLE), yet little is known about how these cells are regulated. In this study, we demonstrated that the frequency of Tfh cells was increased in lupus-prone B6.MRL-Fas(lpr) (B6.lpr) mice and positively correlated to plasma cell proportions and serum total IgG as well as anti-dsDNA antibody levels. Transplantation of mesenchymal stem cells derived from Wharton's jelly of human umbilical cords (hUC-MSCs) ameliorated lupus symptoms in B6.lpr mice, along with decreased percentages of Tfh cells. In vitro studies showed that the differentiation and proliferation of Tfh cells were markedly suppressed by hUC-MSCs. The production of inducible nitric oxide synthase (iNOS) was dramatically upregulated in hUC-MSCs when cocultured with CD4(+) T cells directly, while adding the specific inhibitor of iNOS into the coculture system significantly reversed the inhibitory effect of hUC-MSCs on Tfh cell generation. Interestingly, the efficacy of hUC-MSCs in inhibiting Tfh cells was impaired in the Transwell system, with the reduction of iNOS in both mRNA and protein levels. Taken together, our findings suggest that hUC-MSCs could effectively inhibit Tfh cell expansion through the activation of iNOS in lupus-prone B6.lpr mice, which is highly dependent on cell-to-cell contacts.